Fatigue of Materials III Advances and Emergences in Understanding - Srinivasan, Raghavan; Ashraf Imam, M.; Srivatsan, T.S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume contains papers presented in the third international symposium titled Fatigue of Materials: Advances and Emergences in Understanding held during the Materials Science and Technology 2014 meeting. The book contains contributions from engineers, technologists, and scientists from academia, research laboratories, and industries. The papers are divided into six topical areas: Session 1: Aluminum Alloys Session 2: Ferrous Materials I Session 3: Ferrous Materials II Session 4: Composite Materials Session 5: Advanced Materials Session 6: Modeling The papers cover a broad spectrum of topics that represent the truly diverse nature of the subject of fatigue as it relates to the world of materials.
Keywords: Metals; Materials; Mechanical engineering; Metals and Alloys; Materials Engineering; Mechanical Engineering